2021
DOI: 10.54911/litbang.v21i1.160
|View full text |Cite
|
Sign up to set email alerts
|

Pemetaan Lahan Parkir Dengan Metode Polygon Untuk Pendapatan Asli Daerah Kota Pekalongan

Abstract: Parking is a potential regional revenue which is quite high because it is realized that the number from year to year has increased. Based on data from the Pekalongan City Transportation Service, in 2019 it has reached Rp. 1,205 billion or 75 percent of the target set, which is Rp. 1.6 billion. The parking area managed by the Pekalongan City Government so far has managed 424 points, the types of fees managed are divided into parking fees on the edge of public roads and off-street parking with a composition of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Penelitian sebelumnya dengan judul pemetaan lahan parkir dengan metode polygon untuk meningkatkan pendapatan asli daerah Kota Pekalongan [12], Aplikasi mengatahui titik-titik parkir, memetakan luas lahan parkir dengan metode Poligon pada Google Earth. Penelitian sebelumnya dengan judul model sistem informasi pengelolaan retribusi parkir pada UPTD Parkir Dinas Perhubungan Kota Banjarmasin [13], Sistem informasi berbasis desktop dalam pengelolaan retribusi dan pajak parkir yang dapat mempermudah transaksi perhitungan penerimaan retribusi dan pajak parkir Kota Banjarmasin.…”
Section: Pendahuluanunclassified
“…Penelitian sebelumnya dengan judul pemetaan lahan parkir dengan metode polygon untuk meningkatkan pendapatan asli daerah Kota Pekalongan [12], Aplikasi mengatahui titik-titik parkir, memetakan luas lahan parkir dengan metode Poligon pada Google Earth. Penelitian sebelumnya dengan judul model sistem informasi pengelolaan retribusi parkir pada UPTD Parkir Dinas Perhubungan Kota Banjarmasin [13], Sistem informasi berbasis desktop dalam pengelolaan retribusi dan pajak parkir yang dapat mempermudah transaksi perhitungan penerimaan retribusi dan pajak parkir Kota Banjarmasin.…”
Section: Pendahuluanunclassified
“…However, in (Salsabila, 2018) Findings, trust in the government positively and significantly affects compliance with paying taxes. Another study by (Setiawan et al, 2021), which examined the effect of spiritual intelligence, trust in the government, and social norms at the North Makassar KPP, found that all independent variables had a positive and significant effect partially and simultaneously on the variable motivation to fulfill tax obligations. This means the trust function has a positive and significant relationship with the motivation to pay taxes.…”
Section: Introductionmentioning
confidence: 99%